ITPR1 autoantibody-associated autoimmunity as a cause of newly emerging cognitive decline mimicking Alzheimer's disease: Case report and brief review of the literature - Kunath, Nicolas; Ramfjord, Hermod Arne Bollandsås; Kvisvik, Elisabeth Volden; Konyves-Kolonics, Marton; Rolfseng Grøntvedt, Gøril; Serysheva, Irina I.; Komorowski, Lars; Wildemann, Brigitte; Jarius, Sven (Journal of neuroimmunology, 2025)
Background - Since its first description in 2014, anti-inositol 1,4,5-trisphosphate receptor type 1 (ITPR1, also termed IP3R1) autoimmunity has been recognized as causing a clinically heterogeneous spectrum of symptoms. While first described in patients with autoimmune cerebellar ataxia, this facultative paraneoplastic disease has been associated also with peripheral neuropathy, dysautonomia, sleep disorders, neuropsychiatric/psychotic symptoms, and cognitive decline. - Methods - Retrospective case study. - Results - We report the case of a 58-year-old patient who was admitted with acute confusion, rapidly progressive cognitive decline, and hallucinations. A history of mild cognitive impairment over several years and low cerebrospinal fluid (CSF) amyloid beta-42 and elevated CSF tau protein were suggestive of Alzheimer's disease (AD). However, pleocytosis, intrathecal IgG synthesis and blood-CSF barrier dysfunction prompted screening for antineuronal antibodies, which revealed ITPR1-IgG1/anti-Sj antibodies in both serum and CSF. Brain MRI showed limbic hyperintensities and hippocampal atrophy. No neoplastic disease was found. Immunosuppressive treatment stabilized the disease course but did not lead to symptom improvement. - Conclusions - This case underscores the clinical importance of CSF analysis and testing for anti-neural autoantibodies, including less common reactivities, in case of rapid cognitive decline even in patients with known or suspected neurodegenerative disease, such as AD, with ITPR1 representing a novel autoimmune target antigen.